Analysis of Hospital Discharge Data to Characterize Obstructive Sleep Apnea and Its Management in Adult Patients Hospitalized in Canada: 2006 to 2007. Issue 5 (2010) - Spurr, Kathy F; Morrison, Debra L; Graven, Michael A; Webber, Adam; Gilbert, Robert W
Abstract : BACKGROUND: Diagnosed obstructive sleep apnea (OSA) affects 2% to 7% of middle-age persons worldwide and represents a substantial health care burden. The gold standard for treating OSA in adults is continuous positive airway pressure (CPAP) therapy. Compliance with this treatment is especially important in OSA patients experiencing concomitant acute and chronic disease or illness, and those undergoing procedures associated with sedation, analgesia and anesthesia. OBJECTIVE: To describe the clinical characteristics and management of hospitalized OSA patients in Canada. METHODS: Using the Canadian Institute for Health Information's hospital Discharge Abstract Database (fiscal year 2006/2007), a retrospective cohort study of all acute care patients discharged with a diagnosis that included OSA was performed. RESULTS: An examination of the discharge data of 2, 400, 245 acute care hospital abstracts identified 8823 cases of OSA. The mean age of OSA patients was 45.7 years and 66.5% were men. The most common comorbidities in the adult OSA population were obesity, cardiovascular disease, type 2 diabetes mellitus and chronic obstructive pulmonary disease. In adult OSA patients, the reported surgical intervention rate using uvulopalatopharyngoplasty (9.6%) was much higher than interventional CPAP therapy (4.8%). CONCLUSIONS: Only a small percentage of hospitalized OSA patients were documented as having received CPAP therapy during their stay. Issues relating to the accuracy, specificity and completeness of the Canadian Institute for Health Information's hospital Discharge Abstract Database specific to OSA and its management were identified. Practices pertaining to the reporting, coding and management of hospitalized adult OSA patients warrant further investigation and research.